Designing Resilient Thin Shell Structures : A Comprehensive Approach to Extreme Loading Resistance in Building Foundations - Azizah, Abdul Nassir; Min, Yee Hooi; Arthit, Petchsasithon; Syahrul Fithry, Senin (UKM Press, 2025)
This study aims to explore the potential of thin shell structures as large foundations to improve flood resilience and enhance structural robustness. While thin shell structures have shown promise in resisting various loads, their application as foundations for buildings has not been fully investigated. Thus, this study focuses on designing the necessary reinforcement for a proposed thickness of 304mm. The reinforcement design follows Eurocode 2 guidelines, utilizing T32-300 as the main reinforcement rebar of the thin shell and 5T40 and 4T40 rebars for compression and tension of the ring beam, respectively. R12-150 links are incorporated for added strength and connectivity. This optimized design approach extends the application of thin shell structures beyond lightweight usage, making them viable for withstanding hydrodynamic and seismic loads. This advancement expands possibilities for architects and engineers and improves the resilience of buildings in flood-prone areas. Overall, this study presents a comprehensive design procedure for utilizing thin shell structures as large foundations, contributing to the development of resilient buildings capable of withstanding extreme conditions and safeguarding lives and infrastructure.